Analysis of the profile of physicians enrolled in the “Neurological Conditions in Primary Health Care”: Impacts of Enrollment During the Covid-19 Pandemic - Bretas, Victória Flor (2025)
Introduction: In 2020, concurring with the beginning of the COVID-19 pandemic, Universidade Federal de Ouro Preto (UFOP) representation Universidade Aberta do Sistema Único de Saúde (UNA-SUS) launched the self-learning course “Attention to Frequent Neurological Problems in Primary Care,” with an instructional design strategy designed to the target audience of physicians, with four editions offered between 2020 and 2023. Objective: The aim of this study was to analyze the profile of doctors taking the course in terms of completion rate, region, and gender, as well as to analyze factors that interfere with adherence to the course, with a focus on the impacts of the COVID-19 pandemic. Methods: The behavior of physicians enrolled in the course was analyzed using the enrollment database managed by the UNA-SUS Executive Secretariat, with a quantitative analysis of the correlation between enrollment and completion rates and demographic data over the four years of the course using Python software version 3.12.0. Results: 4,014 physicians were enrolled, with a peak enrolment in 2021 and better completion rates in 2020. The majority of participants were females (61.83%) from the Southeast region (31.98%) and in the 31-35 age range, with a higher volume of enrollments between 26 and 40 years of age. Demographic factors and gender influenced enrollment and completion rates. Across all regions, there was a general increase in both enrollment and completion rates, although there was a drop in the completion rate in the regions during the peak year of the pandemic, followed by a gradual decline in enrollments. Completion rates were 51.4% and 43.6% for males and females respectively in 2020, with a decline in subsequent years, maintaining a parameter common to this profile of self-learning courses. Conclusions: It was evident that both the pandemic and the process of resumption of care had an impact on physicians’ adherence to the course, especially between 2020 and 2021, when there was a reduction in completion rates, and in 2023, when there was a lower number of enrollments; however, completion rates remained at an adequate volume, suggesting that the pedagogical strategies were successful.